Effect of Low Pressure Plasma Treatment on Cotton Fabric Air Permeability and Tear Strength (Damascus University Journal for engineering sciences, 2021)
The aim of this paper is to clarify the effect of low pressure plasma treatment on cotton fabric air permeability and tear strength. A sample of plain woven cotton fabric is treated according to three different times (10 min, 20 min, 30 min), then their air permeability and tear strength are tested. The results of the statistical analysis of data show that plasma treatment has an important impact on these two properties and that the increase of treatment time led to increase fabric air permeability but has no effect on its tear strength.
Keywords: Plasma treatment; low pressure plasma; air permeability; tear strength; woven fabric